Strategic paper for the MEDCO secretariat - Gasmin, Eunice A. (School of Management, University of the Philippines Mindanao, 2008)
The Mindanao Economic Development Council or MEDCo was created on 19 March 1992 by virtue of Executive Order No. 512, signed by then President Corazon C. Aquino, to promote and coordinate the active participation of all sectors to affect the socio-economic development of Mindanao through a wholistic and integrated approach. To provide technical and administration support to the council and its client partners on a full time basis, the MEDCo Secretariat (MS) has been constituted in 1993. The secretariat is responsible for planning, organizing, developing, and supervising all development initiatives that MEDCo oversees. Currently, the Secretariat consists of: Executive Director, Six (6) technical divisions, one (1) finance and administrative division. This Strategic Management Plan aims to provide the MEDCo Secretariat with strategic alternatives which the organization can employ in order to improve organization's delivery of social services, while ensuring its tenure as the prime organization handling Mindanao?s development concerns. As shown in the conceptual framework (Figure 1), the strategy plan commenced with a thorough analysis of the organization's internal and external factors affecting the organization. In broad strokes, the assessment showed that MEDCo, as an organization is above par in its delivery of its services. However, the organization has presenting priorities which are essential in its implementation of mandate such as security of tenure and conservation of human resources. Additionally, the analysis of external factors presented that MEDCo Secretariat has the ability to effectively respond to its external environment. The biggest external factor, however, include political and socio-cultural aspect as the status of the organization, as it is MEDCo is highly affected by political decisions as much as the socio-cultural difficulties presented by cultural division in the island region. Consequently, the organization's organizational anchors, such as vision, mission and long term objectives were assessed as still appropriate based on its relevance to MEDCo?s current mandates. Strategic options were then generated based on the analysis of the organization's strengths, weaknesses, opportunities and challenges, and the interaction of the following. In view of which, several strategy options for the MEDCo Secretariat were proposed, accordingly: 1. Institute MEDCo as a permanent body that serves as the prime consolidator and integrator of accelerated development in Mindanao, 2. Continue partnership with development partners (donors, NGOs, NLAs and PS) in implementing development programs and projects in Mindanao. 3. Capitalize on staff competencies in delivering social services delivery and providing strategic directions to Mindanao stakeholders. Among the strategy options, the institution of the MEDCo as a permanent body that serves as the prime consolidator and integrator of accelerated development in Mindanao was identified to be the core strategy. Hence, implementing program and control systems were formulated. In coming up with the action plan and the monitoring and evaluation mechanisms for the plan, the balanced score card perspectives were used. In consideration of client satisfaction, financial aspect, internal business process, and organization's learning and growth, the essential components in advancing organization's development were covered. For client satisfaction, MEDCo?s niche functions were emphasized, while operational and marketing concerns were placed under the internal business processes. Human resource development was slated under the learning and growth perspective, while the financial perspective was aimed towards growing financial resources available for organization's activities.